2021
DOI: 10.21203/rs.3.rs-968609/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human Papillomavirus Type 16 L2 Gene Sequence Variation Analysis in Indonesian Cervical Cancer Specimens

Abstract: Background: Human papillomavirus type 16 (HPV16) is the most common etiological cause of cervical cancer in Indonesian women. HPV16 L2 genetic variation analysis is important for vaccine strategies of cervical cancer, yet the data in Indonesia is still limited. In this research, we determined the variation of the HPV16 L2 gene sequences in Indonesian cervical cancer specimens. Method: We cross-sectionally observed a total of 23 DNA isolates of HPV16 positive specimens stored in the laboratory of the Center for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Since this mutation is located in the central region of the sequence, far from the important DNA binding domains, the furin cleavage site, and the identified neutralizing epitope regions (all located at the N‐terminal part of the protein), its biological relevance is unclear. The prevalence of this mutation among HPV16 sequences from different lineages is unknown but its presence has been recently observed in 43.5% of HPV16‐positive specimens, mainly classified in lineage A, for which the L2 sequence variations were investigated 21 . While the clinical impact of this mutation was not explored in this latter study, a previous case report had identified this mutation in all HPV16 sequences obtained after the microdissection of a cervical invasive squamous cell carcinoma coexisting with multiple CIN2 and CIN3 lesions in a unique patient 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Since this mutation is located in the central region of the sequence, far from the important DNA binding domains, the furin cleavage site, and the identified neutralizing epitope regions (all located at the N‐terminal part of the protein), its biological relevance is unclear. The prevalence of this mutation among HPV16 sequences from different lineages is unknown but its presence has been recently observed in 43.5% of HPV16‐positive specimens, mainly classified in lineage A, for which the L2 sequence variations were investigated 21 . While the clinical impact of this mutation was not explored in this latter study, a previous case report had identified this mutation in all HPV16 sequences obtained after the microdissection of a cervical invasive squamous cell carcinoma coexisting with multiple CIN2 and CIN3 lesions in a unique patient 22 .…”
Section: Discussionmentioning
confidence: 99%